The "Virtual Digital Twins" Concept in Precision Nutrition - Gkouskou, K.; Vlastos, I.; Karkalousos, P.; Chaniotis, D.; Sanoudou, D.; Eliopoulos, A. G. (Adv NutrAdv NutrAdv Nutr, 2020)
Nutritional and lifestyle changes remain at the core of healthy aging and disease prevention. Accumulating evidence underscores the impact of genetic, metabolic, and host gut microbial factors on individual responses to nutrients, paving the way for the stratification of nutritional guidelines. However, technological advances that incorporate biological, nutritional, lifestyle, and health data at an unprecedented scale and depth conceptualize a future where preventative dietary interventions will exceed stratification and will be highly individualized. We herein discuss how genetic information combined with longitudinal metabolomic, immune, behavioral, and gut microbial parameters, and bioclinical variables could define a digital replica of oneself, a "virtual digital twin," which could serve to guide nutrition in a personalized manner. Such a model may revolutionize the management of obesity and its comorbidities, and provide a pillar for healthy aging.
Gkouskou, KalliopiVlastos, IoannisKarkalousos, PetrosChaniotis, DimitriosSanoudou, DespinaEliopoulos, Aristides GengBethesda, Md.2020/08/10 06:00Adv Nutr. 2020 Nov 16;11(6):1405-1413. doi: 10.1093/advances/nmaa089.
Keywords: *Nutritional Status; Gastrointestinal Microbiome; Humans; Life Style; Obesity; Precision Medicine